Efektivitas model pembelajaran kooperatif Example Nonexample dalam keterampilan menulis Bahasa Jerman mahasiswa - Nurming Saleh; Abd Kasim Achmad; Enung Maria (Seminar Nasional LP2M UNM, 2019)
This article offers a case study of the cooperative learning model example nonexample effectivity on writing skill of second semester German education departement student in faculty of language and literature of Makassar state university. The population was German student on second semester devided into two classes. Class A with 27 sudents as experiment class and class B with 29 students as control class. The data were collected through writing test and analysed by using t-test analysis. The result showed that tcount 5.77 > ttable 2.005 on significant standart 0.05. The result of the study concluded that cooperative learning model example nonexample is effected on second semester of German education departement student writing skill in faculty of language and literature of Makassar state university.